Incorporating Inequality Aversion in Health-Care Priority Setting - Joan Costa-i-Font; Frank Cowell (Center for Economic Studies and ifo Institute (CESifo), 2019)
Although measures of sensitivity to inequality are important in judging the welfare effects of health-care programmes, it is far from straightforward how to elicit them and apply them in health-care decision making. This paper provides an overview of the literature on the measurement of inequality aversion, examines some of the features specific of the health domain that depart from the income domain, and discusses its implementation in health system priority-setting decisions. We find evidence that individuals exhibit a preference for more equitable health distribution, but inequality aversion estimates from the literature are unclear. Unlike the income-inequality literature, standard approaches in the health-economics do not follow a `veil-of-ignorance' approach and elicit mostly bivariate (income-related health) inequality aversion estimates. We suggest some ideas to reduce the disconnect between the income-inequality and health-economics literatures.
Keywords: I19; 330; attitudes to inequality; inequality aversion; health; income; survey data; priority setting